Plan estratégico para mejorar las ventajas competitivas de la corporación chochitos de casa, ubicada en la parroquia Tanicuchi, de la ciudad de Latacunga, período 2015-2018 - Muñoz Hidalgo, Bárbara Yadira (2015)
This research aims to give a strategic direction to the "HOME CORPORATION pussies" with the use of a tool called fourth war (stakeholder analysis / STOKEHOLDERS, PEST trends, competitive analysis and internal analysis) obtaining as a result the critical problems (weaknesses) and competitions advantages (strengths) of the company making the diagnosis of the industry will respond to the various risks generating the same implementing strategic objectives….